Hovhannes Ghazaryan: The Word of God in Chinese - Sargsyan, Armen (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Յովհաննէս Ղազարեանն անուրանալի աւանդ ունի Աստուածաշունչը չինարէն թարգմանելու գործում։ Իրեն անդարդարձող ուսումնասիրութիւններ կան անգլերէն, ռուսերէն, աւելի սակաւ հայերէն։ Սակայն զարմանալիօրէն, անասելի քիչ են չինարէն ուսումնասիրութիւնները։ Ներկայ յօդուածում առաջին անգամ փորձ է արւում չինարէնով ներկայացնելու հայազգի լեզուագէտի գործունէութիւնը։ Ованес Лазарян имеет неоспоримый вклад в деле перевода Библии на китайскей язык. О нем и его трудах есть несколько исследований на английском, русском и гораздо менее на армянском. Однако удивительно, что о нем почти нечго не написано на китайском. В настоящей статье впервые делается попытка представить деятельность армянского Полиглота на китайском языке. Hovhannes Lazaryan has made an undeniable contribution to the translation of the Bible into Chinese. There are several studies about him and his work in English, Russian and much less in Armenian. However, surprisingly, almost nothing has been written about him in Chinese. This article is the first attempt to present the activities of the Armenian Polyglot in Chinese.
Keywords: Historical-Philological Studies